EVALUASI KINERJA MANAJEMEN MELALUI ANALISIS RASIO KEUANGAN PADA INSPEKTORAT PROVINSI SUMATERA UTARA - Nina Andriany Nasution (ITB AAS Indonesia Surakarta, 2024)
This research was conducted to evaluate management performance through financial ratio analysis at the North Sumatra Provincial Inspectorate during the 2023 period, to assess the regional government's ability to use financial ratios, namely the Regional Financial Independence Ratio, Effectiveness Ratio and Efficiency Ratio. This research uses secondary data with a quantitative descriptive approach, data analysis techniques using interactive models utilizing regional financial reports in North Sumatra Province. Based on the results of this research, it shows that the evaluation of management performance through the ratio of the level of independence experiences a Delegative Relationship, that there is no interference from the central government in the province of North Sumatra. Evaluate management performance through the effectiveness ratio with the effective category, that North Sumatra Province is able to realize Regional Original Income. Evaluation of management performance through efficiency ratios with efficient criteria so that regional financial management in North Sumatra Province can achieve targets. Keywords: Management Performance Evaluation, Financial Ratio Analysis, Independence Ratio, Effectiveness Ratio and Efficient Ratio.